Connecting Smart Homes to Healthcare Services for People with Neurodegenerative disorders. - Nour, Mhamed (Transactions on Engineering and Computing Sciences, 2021)
The objective of this research is to provide an approach for the design of what we have called ‘connected homes’ with a study case for elderly people with dementia living alone. These homes would be connected to a center of surveillance for direct and automatic view of multiple status of the day such as patient security and general health indicators (body temperature, heart rate, blood pressure etc.), detect the intake of meals, eating motivation, humor detection prevention of falls, Alcohol consumption detection, safe use of medicines and emergency situations and other Human Activity Recognition (HAR). The model may also predict situations by using past data accumulation. The model could even send alerts in case of emergency. This service would mean that there would minimum intervention from caregivers thanks to the Artificial Intelligence. As a case study, we proposed a new approach for the conception of connected homes for people with dementia to a central office for automatic human activity detection and help and support accordingly. Such conception includes home design concepts according to standard recommendations and the implementation of new added assistive technology tools to permit the automatic surveillance without violating the ethic requirements. Two installation models will be proposed to consider the financial situation of the patient: a unit or appliance at the patient’s home or a home that is connected to a central office.